Illness - Carel, Havi, author.
1 online resource (226 pages)
Keywords: What is illness? Is it a physiological dysfunction, a social label, or a way of experiencing the world? How do the physical, social, and emotional worlds of a person change when they become ill? Can there be well-being within illness? In this remarkable and thought-provoking book, Havi Carel explores these questions by weaving together the personal story of her own illness with insights and reflections drawn from her work as a philosopher. Carel’s fresh approach to illness raises some uncomfortable questions about how we all – whether healthcare professionals or not – view the ill, challenging us to become more thoughtful. Illness unravels the tension between the universality of illness and its intensely private, often lonely, nature. It offers a new way of looking at a matter that affects every one of us.Revised and updated throughout, the third edition of this groundbreaking volume includes a new chapter on organ transplantation. Illness: The Cry of the Flesh will prove essential reading to those studying philosophy, medical ethics, and medical anthropology, as well as those in the healthcare and medical professions. It will also be of interest to individuals who live with illness, and their friends and families.